Islamic Philosophy’s Approach to Environmental Ethics: An Analysis of the Teachings of the Qur’an and Hadith - Ahmad Zuhdi; M. Agus Muhtadi Bilhaq; Lusiana Rahmadani Putri (Yayasan Adra Karima Hubbi, 2024)
Environmental ethics seeks to address humanity’s relationship with the environment, and within Islamic thought, stewardship of nature is rooted in the teachings of the Qur’an and Hadith. These sources provide a moral framework that emphasizes balance, conservation, and responsibility towards the natural world. This study analyzes the principles of environmental ethics in Islamic philosophy, focusing on how the Qur’an and Hadith shape Muslim ethical views on environmental conservation and sustainability. Using a qualitative approach, the research interprets Qur’anic verses and Hadith discussing the human-nature relationship, comparing classical and contemporary Islamic scholarly interpretations. The findings highlight three core principles: Khilafah (stewardship), Mizan (balance), and Amanah (trust). These principles advocate for responsible resource use, sustainability, and a harmonious coexistence between humans and nature. Islamic teachings challenge the anthropocentric perspective, viewing nature as having intrinsic value. The study concludes that Islamic philosophy offers a comprehensive ethical framework for environmental conservation, aligning with modern sustainability efforts. By integrating these teachings into contemporary environmental ethics, a more holistic approach to sustainability can be developed. The research emphasizes the relevance of Islamic principles in addressing today’s environmental challenges and encourages further exploration of religion’s role in promoting environmental stewardship.